Expanding the genetic and phenotypic spectrum of congenital myasthenic syndrome: new homozygous VAMP1 splicing variants in 2 novel individuals - Cotrina-Vinagre, Francisco Javier; Rodríguez-García, María Elena; del Pozo-Filíu, Lucía; Hernández-Laín, Aurelio; Arteche-López, Ana; Morte, Beatriz; Sevilla, Marta; Pérez-Jurado, Luis Alberto; Quijada-Fraile, Pilar; Camacho, Ana; Martínez-Azorín, Francisco (Journal of human genetics, 2024)
We report the cases of two Spanish pediatric patients with hypotonia, muscle weakness and feeding difficulties at birth. Whole-exome sequencing (WES) uncovered two new homozygous VAMP1 (Vesicle Associated Membrane Protein 1) splicing variants, NM_014231.5:c.129+5 G > A in the boy patient (P1) and c.341-24_341-16delinsAGAAAA in the girl patient (P2). This gene encodes the vesicle-associated membrane protein 1 (VAMP1) that is a component of a protein complex involved in the fusion of synaptic vesicles with the presynaptic membrane. VAMP1 has a highly variable C-terminus generated by alternative splicing that gives rise to three main isoforms (A, B and D), being VAMP1A the only isoform expressed in the nervous system. In order to assess the pathogenicity of these variants, expression experiments of RNA for VAMP1 were carried out. The c.129+5 G > A and c.341-24_341-16delinsAGAAAA variants induced aberrant splicing events resulting in the deletion of exon 2 (r.5_131del; p.Ser2TrpfsTer7) in the three isoforms in the first case, and the retention of the last 14 nucleotides of the 3' of intron 4 (r.340_341ins341-14_341-1; p.Ile114AsnfsTer77) in the VAMP1A isoform in the second case. Pathogenic VAMP1 variants have been associated with autosomal dominant spastic ataxia 1 (SPAX1) and with autosomal recessive presynaptic congenital myasthenic syndrome (CMS). Our patients share the clinical manifestations of CMS patients with two important differences: they do not show the typical electrophysiological pattern that suggests pathology of pre-synaptic neuromuscular junction, and their muscular biopsies present hypertrophic fibers type 1. In conclusion, our data expand both genetic and phenotypic spectrum associated with VAMP1 variants.